(untitled) - Plath, David W. (Stanford, Calif., 1980)
The rhetoric of maturity; The fabrication of lives; A suicide cadet; A team captian; A spoiled daughter...
Keywords: Middle-aged persons,Longevity,Người trung niên,Tuổi thọ; Japan,Japan,Nhật Bản,Nhật Bản